The Effect of Drill Reamer Tool on Cutting Force and Temperature when Machining with Different Parameters and Cutting Condition - Rachmat, Haris; Rafai, Noor Hakim (International Journal of Integrated Engineering, 2020)
Normally in manufacturing process, drilling and reaming are separate processes. However a new tool is developed which combined both processes. In this study, the performance of a new drill reamer is studied in terms of cutting force and temperature under internal cooling, external cooling and minimum quantity lubricant (MQL) condition. Three types of tools are used to machine aluminum; 140° twist drill, 140° and 180° drill reamer. Various values of feed were involved while cutting speed and depth of cut are kept constant. From the result it showed that 140° twist drill has produced low cutting (thrust) force and temperature. In addition, low value of cutting force and temperature were also generated when applying low feed and internal cooling condition for all tools.